The SALAMANDER project: SALivAry bioMarkers of mediterraneAN Diet associated with long‐tERm protection against type 2 diabetes. Issue 4 (10th November 2017) - Proctor, G. B.; André, P.; Lopez‐Garcia, E.; Gomez Cabrero Lopez, D.; Neyraud, E.; Feart, C.; Rodriguez Artalejo, F.; García‐Esquinas, E.; Morzel, M.
Abstract: Saliva offers the advantages of simple and non‐invasive sampling and a rich source of biomarkers due to the high diversity of its microbiome, proteome and metabolome. The main objective of the SALivAry bioMarkers of mediterraneAN Diet associated with long‐tERm protection against type 2 diabetes ( SALAMANDER ) project is to identify and validate salivary signatures indicative of healthy dietary choices (adoption of a Mediterranean diet) with a positive long‐term health outcome (protection against type 2 diabetes) throughout adult life. The project will utilise the UK Biobank, a bank of saliva samples with dietary, lifestyle and health‐associated data from 85 000 donors, collected during 2006–2010. UK Biobank data will enable SALAMANDER project researchers to relate past salivary composition and dietary patterns to health status several years later, in order to ascertain the validity of various biomarkers. All subjects will be healthy at baseline and categorised as either healthy (H+) or diagnosed with type 2 diabetes (H−) at follow‐up. Compliance (or not) to the Mediterranean diet (D+, D−) will be evaluated with appropriate adjustment factors ( e.g . physical activity, use of dietary supplements). Within each of the four D/H groups, 50 subjects will be randomly selected and their salivary microbiome, proteome and metabolome will be analysed by 16SrDNA analyses, nano‐LC‐MS/MS of tryptic digests and 1 H NMR, respectively. Integration of analytical data will then be performed to define a multimarker signature of a healthy diet associated with protection against type 2 diabetes. The data obtained from UK Biobank samples will be validated using two other population‐based cohorts of older subjects in Spain ( ENRICA ) and France ( 3‐City Bordeaux ), enabling verification of whether the identified signatures of biomarkers are conserved as ageing proceeds. The SALAMANDER project aims to advance current knowledge and methods in nutritional epidemiology by identifying objective and non‐invasive biomarkers of compliance to a diet associated with prevention of a diet‐related disease. It will also provide information on an ageing population, the salivary profiles of which are poorly documented, especially in relation to diet and health.